Gravity-Based vs. Pump-Assisted Irrigation in Unilateral Biportal Endoscopic Decompression for Lumbar Spinal Stenosis: Effects on Operative Efficiency, Clinical Outcomes, and Complications - Uğur Özdemir; Abdülhalim Akar; Muhammed Fatih Serttaş; Ali Murat Başak; Tunahan Aka (Medicina, 2026)
Background and Objectives: Unilateral biportal endoscopic (UBE) decompression has become an increasingly popular minimally invasive technique for the treatment of lumbar spinal stenosis. Although irrigation management is a critical component of this procedure that may influence operative efficiency and irrigation-related complications, comparative evidence regarding irrigation systems remains limited. Therefore, this study aimed to compare gravity-based and pump-assisted irrigation systems in patients undergoing UBE decompression for lumbar spinal stenosis with respect to clinical and functional outcomes, operative efficiency, and complication rates. Materials and Methods: This retrospective study included 107 patients who underwent single-level UBE decompression for lumbar spinal stenosis between 1 June 2023 and 1 January 2026. Patients were allocated to either the gravity-based (n = 51) or pump-assisted (n = 56) irrigation group according to the availability of the pump-assisted irrigation device at the time of surgery. Pain and functional outcomes were evaluated using the Numeric Rating Scale (NRS) and Oswestry Disability Index (ODI). Operative time, bleeding control time, and perioperative complications were compared between the groups. A mixed-design ANCOVA was used to analyze the changes in clinical outcomes over time. Multivariable linear and logistic regression analyses were performed to identify the independent factors associated with operative time and complications. Results: Significant improvements in the NRS and ODI scores were observed in both groups during follow-up (time effect, p < 0.001 for both), with no significant differences between the irrigation methods (group effect, p > 0.05). Operative and bleeding control times were significantly shorter in the pump-assisted irrigation group (both p < 0.001). Multivariable linear regression analysis demonstrated that pump-assisted irrigation independently reduced operative time by approximately 8 min (p < 0.001), whereas bilateral decompression independently increased operative time by approximately 24.5 min (p < 0.001). Although the overall complication rate was lower in the pump-assisted irrigation group (12.5% vs. 27.5%), the difference was not statistically significant (p = 0.052). Multivariable logistic regression analysis also demonstrated a trend toward a lower risk of complications with pump-assisted irrigation (OR = 0.408, p = 0.096). Conclusions: Pump-assisted irrigation improved operative efficiency by reducing operative and bleeding control times while providing clinical and functional outcomes comparable to those of gravity-based irrigations. Although the reduction in complication rates did not reach statistical significance, pump-assisted irrigation may represent an effective irrigation strategy that improves operative efficiency and may contribute to surgical safety in UBE decompression surgery.